Prevalence of Workplace Violence Against Healthcare Workers During the COVID-19 Pandemic: A Systematic Review and Meta-Analysis - Ramzi, Zhian Salah; Fatah, Proosha Warzer; Dalvandi, Asghar (Frontiers in Psychology, 2022)
Background: A large number of anxious and concerned people refer to health centers during the COVID-19 pandemic, increasing the workload of healthcare workers (HCWs) and violence against these professionals. The present study aimed to estimate the prevalence of workplace violence (WPV) against HCWs during the COVID-19 pandemic. Methods: This systematic review and meta-analysis was conducted via searching in databases such as Scopus, PubMed, and Web of Science, and observational articles reporting the prevalence of WPV against HCWs were selected. Heterogeneity between the studies was assessed using Cochran’s Q test. A random-effects model was used to estimate the prevalence of WPV. Data analysis was performed in the Stata software version 16. Results: In the initial search, 680 articles were identified and screened based on the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) steps. In total, 17 studies with a sample size of 17,207 HCWs were analyzed. The total prevalence of violence was estimated at 47% (95% CI: 34-61%). In addition, the prevalence of physical and psychological violence was 17% (95% CI: 6-28%) and 44% (95% CI: 31-57%), respectively. The prevalence of WPV was higher among physicians (68%; 95% CI: 31-95%) compared to other HCWs. Publication bias was not significant. Conclusion: According to the results, WPV against nurses is prevalent during the COVID-19 pandemic, and intervention measures are required to protect the nursing staff against such violence.